URGENSI PENDIDIKAN KARAKTER DALAM MENGATASI KRISIS MORAL DI KALANGAN SISWA - Slamet Pamuji (PT. Anagata Sembagi Education, 2024)
One reason for the moral crisis among students is the lack of character education taught in schools. Character education is an implanting system of character values that includes components of knowledge (cognitive), feeling (feeling), and action (action) as forms of sexual development and individual conduct. The study aims to provide on the importance of character education in dealing with the moral crisis that prevails among students. Character education is expected to create good citizens as well as morals that match Indonesian citizens' morals. This research method employs a qualitative approach with a study of literature. Research shows that development of The Times, family, peer group, school environment, and social circles have hada major impact on the students' decay of morals. And character education can be the solution to these problems.